2011
DOI: 10.2134/jeq2011.0151
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate‐Nitrogen Losses through Subsurface Drainage under Various Agricultural Land Covers

Abstract: Nitrate-nitrogen (NO₃-N) loading to surface water bodies from subsurface drainage is an environmental concern in the midwestern United States. The objective of this study was to investigate the effect of various land covers on NO₃-N loss through subsurface drainage. Land-cover treatments included (i) conventional corn ( L.) (C) and soybean [ (L.) Merr.] (S); (ii) winter rye ( L.) cover crop before corn (rC) and before soybean (rS); (iii) kura clover ( M. Bieb.) as a living mulch for corn (kC); and (iv) perenni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 26 publications
6
46
2
Order By: Relevance
“…Cover crops have long been used to protect the soil from erosion; however, few studies have investigated the impact of cover crops on tile nitrate losses. Although Qi et al (2011) did not detect a reduction in tile nitrate yield with a rye cover crop, Strock et al (2004) found a modest reduction in tile nitrate yield of 13%, whereas Kaspar et al (2007) found large tile nitrate reductions (59%) using rye as a winter cover crop. Cover crops may be the only practice that can reduce both erosion and tile nitrate yields.…”
Section: Cover Cropmentioning
confidence: 78%
“…Cover crops have long been used to protect the soil from erosion; however, few studies have investigated the impact of cover crops on tile nitrate losses. Although Qi et al (2011) did not detect a reduction in tile nitrate yield with a rye cover crop, Strock et al (2004) found a modest reduction in tile nitrate yield of 13%, whereas Kaspar et al (2007) found large tile nitrate reductions (59%) using rye as a winter cover crop. Cover crops may be the only practice that can reduce both erosion and tile nitrate yields.…”
Section: Cover Cropmentioning
confidence: 78%
“…However, changes in soil NO 3 -N during the spring could be influenced more by site-specific N mineralization, soil moisture, and variability in weather conditions than by RCC alone (Andraski and Bundy, 2008;Krueger et al, 2011). Qi et al (2011) found in Iowa that an RCC reduced NO 3 -N concentrations in tile drainage water in March through June, thus having a positive influence on springtime soil NO 3 -N loss. The RCC effectiveness depended on N rate applied to the prior-year corn, soil management, and weather patterns.…”
Section: Spring Soil Nitrate During the Corn Yearmentioning
confidence: 93%
“…Accumulation of N in vadose zone is commonly observed in arid or semiarid region with high N surplus due to low carbon content, strong mineralization and nitrification abilities, and weak immobilization and denitrification abilities (Scanlon et al, 2008;Walvoord et al, 2003;Zhou et al, 2016). In many humid regions, nitrate would further (Puckett et al, 2011;Qi et al, 2011), Europe (39% of monitoring stations exceeded 25 mg L À1 ) (Angelopoulos et al, 2009;Worrall et al, 2015), India (average concentration exceeded 50 mg L À1 in northern India) (Suthar et al, 2009), and China (28% exceeded 10 mg L À1 ) (Gu et al, 2013;Ju et al, 2004). Although ammonia leaching is usually limited along the soil profile, increasing evidences indicated that leaching from landfills and septic tanks or other sewage disposal plants has resulted in a considerable ammonia accumulation in groundwater, presenting a high potential for storing ammonia in residential groundwater (Umezawa et al, 2009).…”
Section: Legacy Nutrient Dynamics In Vadose Zone/groundwatermentioning
confidence: 99%